Anodic deposition of highly efficient nickel iron oxide electrocatalysts for water oxidation and role of anions in catalyst deposition. (20th August 2022) - Lee, Jihye; Hwang, Dae-Woong; Cho, Wonkyung; Seo, Daye; Won, Sunghwan; Chung, Taek Dong
Abstract: Nickel iron oxide has acquired significant interest as a highly efficient electrocatalyst for the oxygen evolution reaction. Although anodic deposition is beneficial for its preparation, anodically deposited nickel iron oxide presents poor performance, and the detailed mechanism of its formation is ambiguous, limiting its extensive applications. In this study, we examined the anodic deposition of nickel iron oxide using electroanalytical techniques combined with an electrochemical quartz crystal microbalance. In particular, the effects of anions were investigated to determine whether the formation of a nickel iron oxide film sensitively depends on the counter anions of the metal precursors. The anions not only provide buffering to retain the solution pH but also play a significant role in scavenging the surface protons to facilitate the growth of the catalyst film. We established a modified protocol to anodically deposit nickel iron oxide electrocatalysts excellent for water oxidation, with the best ever reported performance. These findings presented important but previously neglected aspects of anodic deposition, providing implications for nonprecious metal electrocatalysts. Graphical abstract: Image, graphical abstract